![SearchIcon](https://vmkt.vedantu.com/vmkt/PROD/png/bdcdbbd8-08a7-4688-98e6-4aa54e5e0800-1733305962725-4102606384256179.png)
How do you factor and simplify ${\sin ^4}x - {\cos ^4}x?$
Answer
450k+ views
Hint: In this question we will be using very basic formulas. We will step by step simplify this equation by using formulas given below. This type of question you should understand because if you understand one question you can solve another question using this method and formulas.
Formula used:
$
\Rightarrow {a^2} - {b^2} = (a + b)(a - b) \\
\Rightarrow {a^4} - {b^4} = {({a^2})^2} - {({b^2})^2} = ({a^2} - {b^2})({a^2} + {b^2}) \\
\Rightarrow {\sin ^2}x + {\cos ^2}x = 1 \\
\Rightarrow 2{\sin ^2}x - 1 = \cos 2x \\
\Rightarrow 1 - 2{\cos ^2}x = \cos 2x \\
\Rightarrow {\cos ^2}x - {\sin ^2}x = \cos 2x \\
$
Complete step-by-step answer:
For solving this question we are using many formulas, which are already studied and also given in the formula used.
So first we will use this formula
${a^4} - {b^4} = {({a^2})^2} - {({b^2})^2} = ({a^2} - {b^2})({a^2} + {b^2})$
Here, the value of a is $\sin x$ and the value of b is $\cos x$.
So after substituting the value of a and b in formula we get,
${\sin ^4}x - {\cos ^4}x = {({\sin ^2}x)^2} - {({\cos ^2}x)^2} = ({\sin ^2}x - {\cos ^2}x)({\sin ^2}x + {\cos ^2}x)$
Now in the above equation we will use ${\sin ^2}x + {\cos ^2}x = 1$.
So after using ${\sin ^2}x + {\cos ^2}x = 1$ we will get,
$ \Rightarrow ({\sin ^2}x - {\cos ^2}x)({\sin ^2}x + {\cos ^2}x) = ({\sin ^2}x - {\cos ^2}x)(1)$
Now, we know that ${\cos ^2}x - {\sin ^2}x = \cos 2x$.
So after substituting the value of ${\cos ^2}x - {\sin ^2}x = \cos 2x$in equation we get,
$ \Rightarrow {\sin ^2}x - {\cos ^2}x = - ({\cos ^2}x - {\sin ^2}x) = - \cos 2x$
So, here the answer of this question is ${\sin ^4}x - {\cos ^4}x = - \cos 2x$
Note: So, we have seen to get an answer to such a type of question you have to follow steps. Because if you make a mistake in one step then you will not get the right answer. And in this type of question finding mistakes is very difficult. So always be focused when we are solving such a type of question.
Formula used:
$
\Rightarrow {a^2} - {b^2} = (a + b)(a - b) \\
\Rightarrow {a^4} - {b^4} = {({a^2})^2} - {({b^2})^2} = ({a^2} - {b^2})({a^2} + {b^2}) \\
\Rightarrow {\sin ^2}x + {\cos ^2}x = 1 \\
\Rightarrow 2{\sin ^2}x - 1 = \cos 2x \\
\Rightarrow 1 - 2{\cos ^2}x = \cos 2x \\
\Rightarrow {\cos ^2}x - {\sin ^2}x = \cos 2x \\
$
Complete step-by-step answer:
For solving this question we are using many formulas, which are already studied and also given in the formula used.
So first we will use this formula
${a^4} - {b^4} = {({a^2})^2} - {({b^2})^2} = ({a^2} - {b^2})({a^2} + {b^2})$
Here, the value of a is $\sin x$ and the value of b is $\cos x$.
So after substituting the value of a and b in formula we get,
${\sin ^4}x - {\cos ^4}x = {({\sin ^2}x)^2} - {({\cos ^2}x)^2} = ({\sin ^2}x - {\cos ^2}x)({\sin ^2}x + {\cos ^2}x)$
Now in the above equation we will use ${\sin ^2}x + {\cos ^2}x = 1$.
So after using ${\sin ^2}x + {\cos ^2}x = 1$ we will get,
$ \Rightarrow ({\sin ^2}x - {\cos ^2}x)({\sin ^2}x + {\cos ^2}x) = ({\sin ^2}x - {\cos ^2}x)(1)$
Now, we know that ${\cos ^2}x - {\sin ^2}x = \cos 2x$.
So after substituting the value of ${\cos ^2}x - {\sin ^2}x = \cos 2x$in equation we get,
$ \Rightarrow {\sin ^2}x - {\cos ^2}x = - ({\cos ^2}x - {\sin ^2}x) = - \cos 2x$
So, here the answer of this question is ${\sin ^4}x - {\cos ^4}x = - \cos 2x$
Note: So, we have seen to get an answer to such a type of question you have to follow steps. Because if you make a mistake in one step then you will not get the right answer. And in this type of question finding mistakes is very difficult. So always be focused when we are solving such a type of question.
Recently Updated Pages
Express the following as a fraction and simplify a class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The length and width of a rectangle are in ratio of class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The ratio of the income to the expenditure of a family class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
How do you write 025 million in scientific notatio class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
How do you convert 295 meters per second to kilometers class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Write the following in Roman numerals 25819 class 7 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Trending doubts
Full Form of IASDMIPSIFSIRSPOLICE class 7 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Fill in the blanks with appropriate modals a Drivers class 7 english CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What are the controls affecting the climate of Ind class 7 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The southernmost point of the Indian mainland is known class 7 social studies CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What were the major teachings of Baba Guru Nanak class 7 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What was the approximate time period of the Indus Valley class 7 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)